The Influence of Work Environment, Salary, and Career De-velopment on Employee Performance Through Employee Commitment at Larissa Aesthetic Centre - Widya Amalia Sasanti; Sunardi Sunardi; Harsono Harsono (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the influence of work environment, salary, and career development on employee performance at Larissa Aesthetic Center through employee commitment as a mediating variable. The importance of optimizing employee performance in supporting business growth requires appropriate efforts and strategies to maximize existing resources in the work environment. Employees who value the work environment because it fosters a sense of well-being and enthusiasm at work. Salary is one of the factors that influences performance, in line with compensation that meets expectations as a form of responsibility in the workplace. Employee career development is seen as a call for progress, where competent workers facilitate the organization in becoming a solution for clients.The method used in this study employs an explanatory approach to uncover the relationships between variables and emphasizes causal numerical data. The study population consists of 65 employees, with the sampling technique using a census, where the entire population serves as the study sample. This research utilizes primary data obtained through questionnaire completion. Secondary data is derived from relevant documentation related to the research topic. Data analysis employs path analysis to test the relationships between research variables. The results of this study indicate that the work environment, salary, and career development have a significant influence on employee performance at Larissa Aesthetic Center, through the support of employee commitment as a mediating variable. The findings of this study can serve as a reference for business actors as a basis for consideration in actions related to human resources.